Desenvolvimento e validação de procedimento analítico para a determinação de compostos organohalogenados em fertilizante orgânico empregando GC-ECD - Wickert, Cristine (2004)
The growing worldwide concern regarding the life quality, especially regarding the preservation and appropriate use of natural resources and quality of food, has reflected on the productive systems. Inside this new tendency, the agroecology bursts as a feasible alternative. The ecological handling of the soil, through the use of animal excrements and of the direct planting, without the pesticides use, seeks the balance and the strengthening of the productive systems. The chicken manure is intensively used with that purpose. However, it is usually associated with materials from the aviaries beds, especially wood shaving, which can contain residues of authorized pesticides to be used as wood preservatives, as some organohalogenated compounds. In the present work, it was developed and validated an analytical procedure for the quantification of pentachlorofenol, 2,4,6-trichlorofenol, 2,4,6- trichloroanisol, 2,4,6-tribromofenol and 2,4,6-tribromoanisol residues in organic fertilizer using Gas Chromatography with Electron Capture Detection (GCECD). Some extraction conditions were appraised, as samples amount, volume and type of extraction solvents. Ultrasound bath and probe, as well as association of mechanical agitation with ultrasound bath, were used as extraction procedures. Several conditions for the purification stages and derivatization of the extracts were studied. The procedure that presented better recovery results was that in which it was used mechanical agitation associated to the ultrasound bath and ethanol/ acetic acid 9:1 (v/v) as solvent for the extraction of the analites. A column containing florisil® and sodium sulphate was used for the purification of the extracts. The derivatization stage was accomplished with anhydride acetic in alkaline medium. The conditions for the chromatographical analysis were: capillary column DB-5 (30 m x 0.25 mm d.i. x 0.25 μm thickness of the film); programming of the temperature of the column oven: 80 °C - 0 min, 200 °C (4 °C min-¹) - 0 min, 300 °C (40 °C min-¹) - 0 min; pressure of the carrier gas 24 psi; volume of injection 2 μL; temperature of the detector 330 °C. In the validation of the procedure they were appraised the following parameters: detection limit (LOD), quantification limit (LOQ), external calibration, linearity, precision (repeatability and intermediary precision) and recovery. LODs in the sample were between 11.3 and 22.5 mg kg-¹ and LOQs between 30.0 and 75.0 mg kg-¹. The curves presented r² > 0,99. The rehearsals of precision supplied acceptable results, with values of RDS between 0.3 and 12.4%. The recoveries were from 83.0 to 110.8%. The results obtained in the validation assays allowed to conclude that the developed procedure is quite appropriate to determine the studied organohalogenated compounds in organic fertilizer. The performance of the procedure was confirmed in commercial samples of organic fertilizer.